Heartstopper. Alice Oseman. - Oseman, Alice (Hodder Children's Books, 2019)
Charlie and Nick are at the same school, but they've never met - until one day when they're made to sit together. They quickly become friends, and soon Charlie is falling hard for Nick, even though he doesn't think he has a chance. But love works in surprising ways, and Nick is more interested in Charlie than either of them realised.